Answer:
x=0
Explanation:
To solve, we need to get the variable, x by itself.
Begin by moving all the numbers to one side of the equation. Perform the opposite of what is being done to the equation.
12=-4(-6x-3)
First, divide both sides by -4, since -4 is being multiplied by -6x-3
12/-4=-4(-6x-3)/-4
-3=(-6x-3)
Add 3 to both sides, since 3 is being subtract from -6x
-3+3=-6x-3+3
0=-6x
Now all the numbers are on one side. x is still not by itself; it is being multiplied by -6. To undo this divide both sides by -6.
0/-6=-6x/-6
0=x